Neoliberalism, capitalist growth models, and the state: An agenda for industrial relations theory. (June 2019) - Howell, Chris
The liberalization of industrial relations has become a generalized phenomenon in advanced capitalist societies. This raises at least three issues that are the subject of this review. First, what is the balance between continuity and change in industrial relations? Second, what is driving change, and in particular, what role is played by shifts in capitalist growth models that have taken place over the last three decades? Third, what does this tell us about the role of political regulation in industrial relations change? This review suggests that scholars need to rethink the role of industrial relations institutions, specifically their ability to shape and mitigate the impact of broad transformations in types of economic growth and the balance of class power. It argues that liberalization of industrial relations and the instability of emerging capitalist growth models highlight the centrality of political regulation and the role of the state in market-making and institution-building.